2007
DOI: 10.1007/s00439-007-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in eight genes of the GH/IGF1 axis does not contribute to adult height variation

Abstract: Stature (adult height) is one of the most heritable human traits, yet few genes, if any, have been convincingly associated with adult height variation in the general population. Here, we selected 150 tag SNPs from eight candidate genes in the growth hormone (GH)/insulin-like growth factor-1 (IGF1) axis (GHR, GHRH, GHRHR, IGF1, IGFALS, IGFBP3, JAK2, STAT5B), and genotyped them in approximately 2,200 individuals ascertained for short or tall stature. Nominally significant tag SNPs were then tested in three addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 69 publications
(76 reference statements)
6
40
0
Order By: Relevance
“…[12][13][14][15] GWAS on height have been reported since 2007 and our group also reported genetic variants for adult height in the Korean population and apparent ancestral differences between Koreans and Europeans. 16 Recently, 54 genetic variants were known to influence the height and all of them were results of studies conducted on adults.…”
Section: Introductionsupporting
confidence: 63%
“…[12][13][14][15] GWAS on height have been reported since 2007 and our group also reported genetic variants for adult height in the Korean population and apparent ancestral differences between Koreans and Europeans. 16 Recently, 54 genetic variants were known to influence the height and all of them were results of studies conducted on adults.…”
Section: Introductionsupporting
confidence: 63%
“…22 These results 28,29 A genome-wide association study from Korea reported a possible association between an IGF1 single-nucleotide polymorphism and height, which did not achieve genome-wide significance. An association of the same single-nucleotide polymorphism with height for children with idiopathic short stature was reported by the same study.…”
mentioning
confidence: 91%
“…Importantly, this fact must be analyzed by functional studies, but bearing in mind that in vitro results are not always predictive of a clinical effect (3).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these various disorders need to be excluded before the diagnosis of ISS can be made. These mutations include defects in GH-1, growth hormone-releasing hormone receptor (GHRHR), GH receptor gene (GHR), as well as various other genes, such as signal transducer (STAT5B), IGF-I and IGF-acid labile subunit (ALS), and so on (3). With an increasing number of reports on these gene defects, it has become evident that there is no strict geno/phenotype correlation; furthermore, phenotypes are highly variable.…”
Section: Introductionmentioning
confidence: 99%